2020
DOI: 10.4314/ijbcs.v13i6.23
|View full text |Cite
|
Sign up to set email alerts
|

Malaria prevalence and In vitro susceptibility of <i>Plasmodium falciparum</i> isolates to selected antimalarial agents in Bauchi, Nigeria

Abstract: Malaria has been reported to be a high bio burden disease in sub-Sahara African Countries. About 50% has been associated with at least one episode of malaria while children were reported with two or four episodes. This study reports the prevalence of malaria and susceptibility pattern of Plasmodium falciparum isolates from patients visiting Specialist Hospital Bauchi, Nigeria to reportedly prescribed antimalarial agents in Bauchi. Information on malaria patients and antimalarial drugs prescribed to the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Malaria is one of the leading causes of infections and deaths recording 455,000 deaths in 2017 worldwide with most deaths in sub-Saharan Africa (WHO, 2018). The increasing prevalence of resistant strains of plasmodium and difficulties to access and buy effective antimalarial are the major factors responsible for the increasing mortality rates that occur mainly in Africa (Atang et al 2019). Hence the need to use medicinal plants as complementary and alternative medicine for malaria treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is one of the leading causes of infections and deaths recording 455,000 deaths in 2017 worldwide with most deaths in sub-Saharan Africa (WHO, 2018). The increasing prevalence of resistant strains of plasmodium and difficulties to access and buy effective antimalarial are the major factors responsible for the increasing mortality rates that occur mainly in Africa (Atang et al 2019). Hence the need to use medicinal plants as complementary and alternative medicine for malaria treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Umar et al (2017), similarly, reported 38.0% of P. falciparum isolates to be resistant to artemether in Kaduna, Nigeria. Another research conducted in Bauchi, North-eastern Nigeria by Atang et al (2019) also reported 14.12% resistance of P. falciparum to artemether. Artemisinin derivatives were generally reported to be very active against malaria parasites until some few years ago when P. falciparum resistance to artemisinin was detected in five countries of the Greater Mekong sub-region namely Cambodia, Lao People's Democratic Republic, Myanmar, Thailand and Vietnam (WHO, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…The higher prevalence noted by Ezebialu in Nnewi may represent environmental differences in the study populations, as previous studies in Nnewi and Bauchi noted a higher prevalence of malaria in Nnewi than in Bauchi, both in Nigeria. 27, 28 Plasmodium falciparum was the only species found in the placentae of the primigravidae. This finding is consistent with the findings of studies by Ezebialu et al 16 and Fehintola et al, 19 who used placental tissue histology and microscopy of placental blood, respectively.…”
Section: Discussionmentioning
confidence: 99%